Perhitungan Harga Pokok Produksi dengan Metode Full Costing untuk Menentukan Harga Jual Minuman Boba Brown Sugar pada Brand “Meenum” - Sari Ayu; Suroso Suroso; Reza Agustur; Fadillah Ashary (Universitas 45 Surabaya, 2025)
It is important to pay attention to the calculation of the cost of production, due to increasing competition between businesses, creating quality products at fairly competitive prices. This research aims to determine the calculation of the cost of production in determining the selling price of Boba Brown Sugar beverage products under the